2022
DOI: 10.1155/2022/9802222
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Polypropylene-Fiber-Reinforced High-Performance Concrete Based on the Response Surface Method

Abstract: Polypropylene fibers are added to concrete to improve the toughness of the material. Manufactured sand and fly ash with high content are used to reduce the impact on the environment and cost. The response surface method (RSM) was used to design the test and study the mechanical and bending properties of polypropylene-fiber-reinforced high-performance concrete (PPFHPC). Three process variables, including the content of polypropylene fiber (1%, 1.5%, and 2%), content of fly ash (45%, 60%, and 75%), and water-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, it was analyzed upon performing the compressive strength on the specimens that the masks were holding the fragments of concrete and helped the concrete fragments to adhere even upon failure. Therefore, upon adding face masks to concrete, the resultant concrete mix showed better resistance towards cracking and improved performance of the resultant concrete [14]. The following graph was formed from the compressive strength values collected in the laboratory (Fig.…”
Section: Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was analyzed upon performing the compressive strength on the specimens that the masks were holding the fragments of concrete and helped the concrete fragments to adhere even upon failure. Therefore, upon adding face masks to concrete, the resultant concrete mix showed better resistance towards cracking and improved performance of the resultant concrete [14]. The following graph was formed from the compressive strength values collected in the laboratory (Fig.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The addition of fiber such as polypropylene fiber, polyethylene fiber, and so on into the concrete has been a new concept recently [14], Addition of such fibers to concrete help to improve the uniformity of the mix, strength, and durability [14]. It also helps in improving properties such as reduction in shrinkage cracks and helps in improving wear resistance, impermeability, and tensile strength of the resultant matrix [14]. The polypropylene fiber in disposable face masks contributes significantly to the tensile strength of the face masks [15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of synthetic organic fibers, represented by polypropylene fiber (PPF), has made great progress. Song et al [18] conducted an experimental study on the mechanical and flexural properties of polypropylene fiber-reinforced concrete, and the results showed that the fibers can inhibit crack expansion and avoid brittle damage when cracks appear in the concrete. Yao et al [19] investigated the mechanical properties of polypropylene fiber-reinforced concrete, and the results showed that the flexural strength, tensile strength, and fracture toughness of polypropylene fiber-reinforced concrete were significantly higher than those of ordinary concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of short fibers and electronic wastes has a significant benefit over the overall performance of conventional concrete like tensile strength, compression strength, durability, load bearing capacity, and post crack. (1)(2)(3)(4)(5)(6) Also, a poor tensile and flexural response of the geo-polymer concrete composites (7) and Cement-tailings matrix composites (CTMC) (8) can be enhanced with the inclusion of natural and synthetic fibers. The banana skin power (BSP) as cement replacement and coir fiber (CF) as filler in self-compacting concrete (SCC) showed enhancement up to 7% in compression strength for 0.4% of BSP and 0.5% of CF adding in SSC.…”
Section: Introductionmentioning
confidence: 99%